Stališča delodajalcev do zaposlovanja oseb s težavami v duševnem zdravju - Plavšić, Jasmina (Rehabilitacija (Ljubljana), 2018)
Background: The practice at our vocational rehabilitation center suggests that persons with mental health problems (MHP) are more difficult to employ and it is harder for them to find work. The purpose of our study was to survey the employers' attitudes towards employing people with MHP. Our hypothesis was that employers are predominantly disinclined to employ people with MHP. Methods The participants were representatives of different employers - various companies, societies and organisations who either had not or have had experience with employing people with MHP. The survey was condacted online through the Survey Planet website. Employers from our network in Maribor, Murska Sobota and Ptuj areas were encouraged to participate. The survey had twenty statements that summarised prejudice regarding the employment of people with MHP; the ansewer had to be given on a five-point scale (from "complete disagree" to "completely agree"). Results We obtained 58 completed surveys from 58 different employers. More than a half of the responses represented the view of persons employed in managerial jobs. Conclusions The results indicate that the employers are still not fully confident when it comes to employing people with MHP. They fear that the employment of persons with MHP may represent a risk in terms of business damage. Nevertheless, the proportion of employers with social responsibility awareness is increasing. The view that persons with MHP get fewer job opportunities in comparison with other job seekers is strongly expressed among the employers. The results indicate that the stigma is still present in daily practice. In the future, it will be necessary to remove the negative effects of stigma on individual as well as on the collective level. The hypothesis that the employers are predominantly disinclined to employ people with MHP was not confirmed.
Keywords: delodajalci; disabled persons; duševno zdravje; employers; employment; mental health; mental health problems; osebe z zmanjšanimi zmožnostmi; Rehabilitation, Vocational; zaposlovanje